[18F]Fluorophenylazocarboxylates: Design and Synthesis of Potential Radioligands for Dopamine D3 and μ‑Opioid Receptor. - Nebel, Natascha; Strauch, Brigitte; Maschauer, Simone; Lasch, Roman; Rampp, Hannelore; Fehler, Stefanie; Bock, Leonard; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus; Prante, Olaf (ACS Omega, 2017)
18F-Labeled building blocks from the type of [18F]fluorophenylazocarboxylic-tert-butyl esters offer a rapid, mild, and reliable method for the 18F-fluoroarylation of biomolecules. Two series of azocarboxamides were synthesized as potential radioligands for dopamine D3 and the μ-opioid receptor, revealing compounds 3d and 3e with single-digit and sub-nanomolar affinity for the D3 receptor and compound 4c with only micromolar affinity for the μ-opioid receptor, but enhanced selectivity for the μ-subtype in comparison to the lead compound AH-7921. A "minimalist procedure" without the use of a cryptand and base for the preparation of 4-[18F]fluorophenylazocarboxylic-tert-butyl ester [ 18 F]2a was established, together with the radiosynthesis of methyl-, methoxy-, and phenyl-substituted derivatives ([ 18 F]2b-f). With the substituted [18F]fluorophenylazocarbylates in hand, two prototype azocarboxylates radioligands were synthesized by 18F-fluoroarylation, namely the methoxy azocarboxamide [ 18 F]3d as the D3 receptor radioligand and [ 18 F]4a as a prototype structure of the μ-opioid receptor radioligand. By introducing the new series of [18F]fluorophenylazocarboxylic-tert-butyl esters, the method of 18F-fluoroarylation was significantly expanded, thereby demonstrating the versatility of 18F-labeled phenylazocarboxylates for the design of potential radiotracers for positron emission tomography .
EVALuna2:34730

Fast and efficient 18F-labeling by [18F]fluorophenylazocarboxylic esters - Fehler, Stefanie; Maschauer, Simone; Höfling, Sarah; Bartuschat, Amelie; Tschammer, Nuska; Hübner, Harald; Gmeiner, Peter; Prante, Olaf; Heinrich, Markus (Chemistry - A European Journal, 2014)
Introduction of [(18) F]fluoride ion into the aromatic core of phenylazocarboxylic esters was achieved in only 30 seconds, with radiochemical yields of up to 95 % (85(±10) %). For labeling purposes, the resulting (18) F-substituted azoester can be further converted in radical-arylation reactions to give biaryls, or in substitutions at its carbonyl unit to produce azocarboxamides. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-04-14:Pub.2014.nat.dchph.lphch.fastan

How the Structural elucidation of the natural product Stephanosporin led to new developments in aryl radical and medicinal chemistry - Fehler, Stefanie; Heinrich, Markus (Synlett, 2015)
The intent of this account is to provide a focused overview of recent developments in aryl radical chemistry, especially extensions and applications of the Meerwein arylation and the Gomberg-Bachmann reaction. Although most of the reactions and methods described were discovered on the basis of earlier findings made by our group or logically depend on newly discovered reactivities or mechanistic principles, the rapid evolution of radical chemistry can nevertheless be traced back to the behavior of the natural product stephanosporin, which is capable of liberating 2-chloro-4-nitrophenol via an aryl radical intermediate.
Keywords: arylations; diazonium compounds; Gomberg-Bachmann reactions; hydrazines; Meerwein reactions; radical reactions

Radical arylation of tyrosine residues in peptides - Fehler, Stefanie; Pratsch, Gerald; Östreicher, Christiane; Fürst, Michael; Pischetsrieder, Monika; Heinrich, Markus (Tetrahedron, 2016)
The radical arylation of the phenolic side chain of tyrosine in peptides was investigated. Aryl radicals were generated from aryldiazonium salts using titanium(III) chloride as stoichiometric reductant. Due to the high selectivity with which 3-aryltyrosine derivatives were formed, this reaction type represents a new strategy for the direct functionalization of peptides.
Keywords: Arylation; Diazonium; Peptide; Radical reaction; Tyrosine

Synthesis and evaluation of fluoro substituted pyridinylcarboxamides and their phenylazo analogues for potential dopamine D3 receptor PET imaging - Nebel, Natascha; Maschauer, Simone; Bartuschat, Amelie; Fehler, Stefanie; Hübner, Harald; Gmeiner, Peter; Kuwert, Torsten; Heinrich, Markus; Prante, Olaf; Hocke, Carsten (Bioorganic & Medicinal Chemistry Letters, 2014)
A series of fluoro substituted pyridinylcarboxamides and their phenylazo analogues with high affinity and selectivity for the dopamine D3 receptor was synthesized by the use of 6-fluoropyridine-3-carbonyl chloride (1) and fluorophenylazocarboxylic ester (2). Several of these compounds (9a-e and 10a-h) have been evaluated in vitro, among which 9b, 10a, 10c and 10d proved to have at least single-digit nanomolar affinity for D3. They also exhibit considerable selectivity over the other dopamine receptor subtypes and noteworthy selectivity over the structurally related serotonin receptor subtypes 5-HT1A and 5-HT2, offering potential radiotracers for positron emission tomography.
UnivIS-Import:2015-04-14:Pub.2014.nat.dchph.lphch.synthe_8
Keywords: Azoester; D3 receptor; Dopamine; Fluorine; Fluoroarylation; PET

Synthesis, Radiosynthesis and Biological Evaluation of Buprenorphine-Derived Phenylazocarboxamides as Novel mu-Opioid Receptor Ligands - Krüll, Jasmin; Fehler, Stefanie; Hofmann, Laura; Nebel, Natascha; Maschauer, Simone; Prante, Olaf; Gmeiner, Peter; Lanig, Harald; Hübner, Harald; Heinrich, Markus (ChemMedChem, 2020)
Targeted structural modifications have led to a novel type of buprenorphine-derived opioid receptor ligand displaying an improved selectivity profile for the mu-OR subtype. On this basis, it is shown that phenylazocarboxamides may serve as useful bioisosteric replacements for the widely occurring cinnamide units, without loss of OR binding affinity or subtype selectivity. This study further includes functional experiments pointing to weak partial agonist properties of the novel mu-OR ligands, as well as docking and metabolism experiments. Finally, the unique bifunctional character of phenylazocarboxylates, herein serving as precursors for the azocarboxamide subunit, was exploited to demonstrate the accessibility of an F-18-fluorinated analogue.
Keywords: azo compounds; bioisosters; buprenorphine; opioid receptors; radiosynthesis